Effect of alterations in the thyroid state on the intrinsic contractile properties of isolated rat skeletal muscle - Gold, Herman K. (1970)
Contractile properties of soleus muscles isolated from 31 euthyroid (EU), 20 hyperthyroid (HT), and 18 myxedematous (MY) rats were studied in a myograph. At 100 stimuli/sec maximum isometric tension was essentially identical in EU (17.2 ±0.5 g/mm(2)) and HT (17.7 ±0.5 g/mm(2)) muscles, but was significantly depressed in MY muscles (11.5 ±0.7 g/mm(2)). The rate of tension development was increased in HT (103 ±4.5 g/sec per mm(2)) as compared to both EU (86.2 ±4.6 g/sec per mm(2)) and MY (38.4 ±2.2 g/sec per mm(2)) muscles, while the duration of the active state was shortened in HT (77.1 ±2.3 msec) as compared to EU (105.1 ±1.1 msec) muscles and was prolonged in MY muscles (153.3 ±6.0 msec). The mean rate of isometric relaxation was 26.5 ±4.9 g/mm(2) per sec in EU muscles, more rapid in HT muscles (33.1 ±1.3 g/sec per mm(2)), and slower in MY muscles (16.0 ± g/mm(2) per sec). The fusion frequency was greater in HT muscles, averaging 68.5 ±3.6 stimuli/sec compared to EU muscles (38.1 ±1.2 stimuli/sec) and to MY muscles (33.3 ±4.0 stimuli/sec). At 40 stimuli/sec tension averaged 16.4 ±0.8 g/mm(2) in EU muscles while at the same frequency tension was reduced in HT muscle, averaging 14.2 ±0.5 g/mm(2). All differences were significant (P < 0.01). In conclusion, HT and MY result in profound alterations in the intrinsic contractile properties of skeletal muscle. While tension in HT muscles is maintained in vitro at a stimulus frequency of 100 stimuli/sec, the reduction in duration of active state may lower tension in vivo by preventing complete fusion of contractile events. In MY tension is reduced as a consequence of the lowered intensity of the active state. These changes explain, at least in part, the weakness of muscle activity in both HT and MY.